Analysis of local regulations for the enforcement of the Environmental Subpoena in Florencia, Caquetá, Colombia - Plazas Vargas, Luz Stella; Montoya Leyton, Luis Carlos (DIXI, 2017)
Purpose: the work consisted in the analysis of local regulations for the enforcement of the Environmental Subpoena in Florencia, Caquetá (Colombia). For this, municipal agreements 024 of 2009 and 013 of 2011 were taken into account, as well as the community’s degree of knowledge during the three-year implementation of the Environmental Subpoena, in order to determine the causes for the low enforceability of the subpoena. This will contribute to a possible amendment to the municipal agreements described, thus improving enforceability and implementation of the regulation. Description: in the performance of the work, the municipal agreements on the subject were collected, reviewed and analyzed, and 50 surveys were randomly applied to residents of the downtown area of the city in order to evaluate their knowledge of the environmental subpoena. Point of view: the result obtained reflects that 60 % of the population surveyed wants citizen education, enforcement of the subpoena, recycling, separation at source and prohibition to throw garbage; likewise, it was obtained that, on average, 37 people (equivalent to 74 %) claimed to be aware of the existence of actions that merit a subpoena; the rest (13 people, equivalent to 26 %) responded not knowing about the issue. Conclusions: this shows that the low enforcement of the Environmental Subpoena is due, above all, to the population’s minimum social responsibility, the failure to approve agreements, and the lack of empowerment on the part of those responsible for its regulation, implementation and enforcement.